Single-Actuator-Based Lower-Limb Soft Exoskeleton for Preswing Gait Assistance. (13th July 2020) - Hsieh, Ming-Hwa; Huang, Yin Hsuan; Chao, Chia-Lun; Liu, Chien-Hao; Hsu, Wei-Li; Shih, Wen-Pin
Abstract : In this research, we proposed a lower-limb soft exoskeleton for providing assistive forces to patients with muscle weakness during the preswing phase of a gait cycle. Whereas conventional soft exoskeletons employ two motors to assist each leg individually, we designed a single motor for actuation. Our design assists hip flexion for light weights and prevents some slip problems that can arise from rotary motors. The actuation mechanism was based on a pulley system that converted the power supplied by the single motor into linear reciprocating motions of a slider. When the single motor rotated, the slider moved linearly, first in one direction and then in the opposite direction. The slider pulled knee braces through cables with an assistive force of 100 N. The actuation was triggered when the system detected that the backward swing of the wearer's thigh had ended. A prototype was designed, fabricated, and examined with 7 subjects (average age, 24). Subjects were measured while they wore our exoskeleton in power-off and power-on modes. Comparisons proved that wearing the exoskeleton caused a negligible deviation of gait, and that the soft exoskeleton could reduce metabolic cost during walking. The research results are expected to be beneficial for lightweight soft exoskeletons and integration with exosuits that provide assistive forces through the wearer's entire gait.